Feasibility of fat fraction quantification by measuring J-coupling related signal modulation in multi echo fast spin echo sequences. (September 2016) - Nikiforaki, K.; Boursianis, T.; Manikis, G.C.; Marias, K.; Karantanas, A.; Maris, T.G.
Abstract : Introduction: Echo spacing in Fast Spin Echo techniques can affect signal intensity mainly of fatty tissue and is presented as effectively prolonged T2 relaxation time (magnetic fat liquefaction). Purpose: The aim of this study is to measure signal intensity in multi echo Fast Spin Echo techniques with variable echo spacing in order to examine the feasibility of fat quantification from J-coupling related signal modulation. T2 maps were calculated from all different acquisition schemes. Materials and methods: A phantom containing porcine fat, vegetable oils, gadolinium doped agarose gels that mimic fat magnetic relaxation properties, double distilled water at controlled temperature of 36–38 °C was scanned at 1.5 T utilizing a single slice multi echo SE technique with equidistant echoes of variable TE intervals (6.7–40 ms). Results: Fat signal modulation as a function of echo spacing varied significantly between short and long echo spacing acquisitions (28.97–56.26%) and this dependence could be approximated by a linear sequence ( Δ S fat = S short ESP - S long ESP = 3.38*n*TE + 27.18, residual 7, 88 for n ranging from 1 to 12) for a wide range of routinely used TEs in clinical practice (13.4–160.8 ms) while effect on water was minimal ( Δ S water = 22.11%, SD for same TE range: 0.53). Difference of calculated T2 relaxation times between sequences with different echo spacing ranged from 9.5 to 35%. Conclusion: Echo spacing in MESE sequences may serve as a metric of signal manipulation and fat quantification. Bright fat sequences should be avoided for T2 relaxation parametric maps.